The Effectiveness of Three-Dimensional Solar System Teaching Aids in Developing Sixth-Grade Students' Critical Thinking Skills - Juwariyah, Siti; Desy Aprima (Papanda Publisher, 2025)
Twenty-first-century education emphasizes the importance of critical thinking skills, yet the utilization of teaching aids in elementary science education remains suboptimal. This study examined the effect of solar system teaching aids on sixth-grade students' critical thinking skills at SD Negeri 01 Tekorejo. A quasi-experimental one-group pretest-posttest design was employed with 30 students selected through total sampling. The instrument consisted of a five-item essay test developed based on critical thinking indicators: identifying problems, providing arguments, evaluating arguments, drawing conclusions, and formulating solutions. Data were analyzed using descriptive statistics and the Wilcoxon Signed-Rank Test due to non-normal data distribution. Results showed a significant increase in mean scores from 11.60 (pretest) to 16.00 (posttest), with a significance value of 0.013 (p < 0.05), indicating that teaching aids significantly enhanced students' critical thinking skills. The three-dimensional solar system models facilitated transformation of abstract astronomical concepts into concrete representations, enabling students to engage in hands-on exploration, collaborative discussion, and analytical reflection. These findings align with Piaget's cognitive development theory, demonstrating that concrete manipulatives effectively support elementary students at the concrete operational stage. This study contributes empirical evidence for the efficacy of physical teaching aids in developing higher-order thinking skills and recommends systematic integration of concrete instructional media to strengthen conceptual understanding and support twenty-first-century competencies in elementary science education.